HD-FFQ to detect nutrient deficiencies and toxicities for a multiethnic Asian dialysis population - Md Ali, Mohammad Syafiq; Zu, Wei Yeak; Khor, Ban Hock; Sahathevan, Sharmela; Sualeheen, Ayesha; Lim, Jun Hao; Adanan, Nurul Iman Hafizah; Abdul Gafor, Abdul Halim; Zakaria, Nor Fadhlina; Khosla, Pramod; Karuppiah, Thilakavathy; Mat Daud, Zulfitri 'Azuan (Multidisciplinary Digital Publishing Institute, 2020)
A rapid and reliable tool appropriate to quantifying macronutrient and micronutrient intakes in diets consumed by Malaysian hemodialysis (HD) patients is lacking. We aimed to develop and validate a novel HD-food frequency questionnaire (HD-FFQ) to assess habitual nutritional intakes of HD patients with diverse ethnic backgrounds. This study was conducted in three phases. In Phase I, a HD-FFQ comprising 118 food items was developed using 3-day diet recalls (3DDR) from 388 HD patients. Phase II was the face and content validation using the Scale-Content Validity Index (S-CVI). After successfully developing the FFQ, Phase III tested relative validation against a reference method, the 3DDR. Results from Phase III showed that the mean difference for absolute intakes of nutrients assessed by HD-FFQ and 3DDR were significant (p < 0.05). However, there was a significant correlation between the HD-FFQ and reference method ranging from 0.35–0.47 (p < 0.05). Cross-quartile classification showed that <10% of patients were grossly misclassified. In conclusion, the HD-FFQ has an acceptable relative validity in assessing and ranking the dietary intake of the HD patients in Malaysia.